The Feminine Self-Concept of Muscular Women on the Social Media Platform Instagram - Fitria, Namira; Subhan, Arief; Jamalullail, Jamalullail (CV. Social Politic Genius (SIGn), 2025)
Historically, the female body has been the object of patriarchal beauty standards that glorify thinness. This research aims to examine how muscular women negotiate and construct their self-concepts through symbolic interactionism on Instagram. This study employs a qualitative, interpretive approach. Primary data collection was conducted through participant observation and the analysis of social media content from six active members of the Celebrity Fitness center in Jakarta. All data were comprehensively analyzed using thematic analysis techniques. The results indicate that muscular women initiated their identity negotiation in the physical space by rejecting conventional beauty standards. This physical capital, integrating masculine strength and feminine softness, was strategically represented in the virtual space. They produced significant symbols through stages of visual curation and verbal discourse to dismantle stereotypes of female physical weakness. This digital representation culminated in a psychological alignment process. The reception of quantitative appreciation through like buttons and qualitative appreciation in comment sections acted as external validation instruments. This social network support triggered an increase in self-esteem and facilitated their achieving an optimal state of psychological congruence. The real self, which had densified, completely aligned with the ideal self projected on the virtual display. This study concludes that digital validation acts as the ultimate instrument perfecting the autonomy and existence of muscular women. Practically, the broader society is urged to cultivate a more inclusive space of tolerance to celebrate the diversity of women’s physical expressions without the shackles of obsolete gender constructs.